2001
DOI: 10.1093/nar/29.6.1352
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the gene-dense ACHE/TFR2 region on human chromosome 7q22 with the orthologous region on mouse chromosome 5

Abstract: Chromosome 7q22 has been the focus of many cytogenetic and molecular studies aimed at delineating regions commonly deleted in myeloid leukemias and myelodysplastic syndromes. We have compared a gene-dense, GC-rich sub-region of 7q22 with the orthologous region on mouse chromosome 5. A physical map of 640 kb of genomic DNA from mouse chromosome 5 was derived from a series of overlapping bacterial artificial chromosomes. A 296 kb segment from the physical map, spanning ACHE: to Tfr2, was compared with 267 kb of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 75 publications
0
59
0
Order By: Relevance
“…As noted above, significant variation in the level of sequence conservation between human and mouse from locus to locus has been reported in several studies of long DNA sequences of single loci (Hardison et al 1991(Hardison et al , 1997Koop 1995;DeBry and Seldin 1996;Gött-gens et al 2001;Shiraishi et al 2001;Wilson et al 2001) and in comparative studies of gene sequences in these and other mammals (Wolfe et al 1989;Bernardi 1993Bernardi , 1995Casane et al 1997;Matassi et al 1999;Williams and Hurst 2000;Lercher et al 2001;Castresana 2002a,b), albeit with some dissenting analysis (Williams and Hurst 2000;Kumar and Subramanian 2002). With ∼700 4D sites/Mb and 50,000 AR sites/Mb genome-wide, we were able to do a much larger scale study of regional variation in rates of substitution, and found correlated fluctuations in regional substitution rates for both types of sites.…”
Section: Large-scale Regional Variation and Covariation In Rates Of Smentioning
confidence: 90%
“…As noted above, significant variation in the level of sequence conservation between human and mouse from locus to locus has been reported in several studies of long DNA sequences of single loci (Hardison et al 1991(Hardison et al , 1997Koop 1995;DeBry and Seldin 1996;Gött-gens et al 2001;Shiraishi et al 2001;Wilson et al 2001) and in comparative studies of gene sequences in these and other mammals (Wolfe et al 1989;Bernardi 1993Bernardi , 1995Casane et al 1997;Matassi et al 1999;Williams and Hurst 2000;Lercher et al 2001;Castresana 2002a,b), albeit with some dissenting analysis (Williams and Hurst 2000;Kumar and Subramanian 2002). With ∼700 4D sites/Mb and 50,000 AR sites/Mb genome-wide, we were able to do a much larger scale study of regional variation in rates of substitution, and found correlated fluctuations in regional substitution rates for both types of sites.…”
Section: Large-scale Regional Variation and Covariation In Rates Of Smentioning
confidence: 90%
“…Sequences spanning that region in human, mouse, dog, armadillo, elephant, and opossum were aligned with BLASTZ (Schwartz et al 2003), and the alignments interactively inspected using the laj program (Wilson et al 2001), both of which are freely available at http://www.bx.psu. edu/miller_lab/.…”
Section: Identification Of Diagnostic Retroelement Insertionsmentioning
confidence: 99%
“…In this mode, one initially uses GALA to query across multiple fields and genes to find the desired results, and then upon request, the program automatically connects the user to the browser so that its graphical display is used to summarize desired features of the region and its surrounding context. For examining sequence alignments and annotations interactively, query results can be ported automatically to our Laj alignment viewer (Wilson et al 2001), as illustrated in Figure 3. Finally, the distribution of query results across the chromosome can be examined as a bar graph.…”
Section: Output Formatsmentioning
confidence: 99%
“…Laj (Local Alignments with Java) is a Java applet that allows the user to interactively examine pairwise alignments and associated annotations in a graphical setting (Wilson et al 2001). The version executed by GALA will display percent identity plots (pips) (Schwartz et al 2000), text representations of the alignments, a schematic diagram showing the locations of exons and repeats, annotation links to other Web sites containing additional information about particular regions, and colored shading to highlight areas of interest.…”
Section: Laj Alignment Viewermentioning
confidence: 99%
See 1 more Smart Citation